New poly(1,3,4-oxadiazole)s bearing pentadecyl side chains: synthesis and characterization - More, Arvind S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2012)
The 4-[4'-(Hydrazinocarbonyl)phenoxy]-2-pentadecylbenzohydrazide was polycondensed with aromatic diacid chlorides viz., terephthalic acid chloride (TPC), isophthalic acid chloride (IPC), and a mixture of TPC : IPC (50 : 50 mol %) to obtain polyhydrazides which on subsequent cyclodehydration reaction in the presence of phosphoryl chloride yielded new poly(1,3,4-oxadiazole)s bearing flexibilizing ether linkages and pentadecyl side chains. Inherent viscosities of polyhydrazides and poly(1,3,4-oxadiazole)s were in the range 0.530.66 dL g(-1) and 0.490.53 dL g(-1), respectively, indicating formation of medium to reasonably high molecular weight polymers. The number average molecular weights (M-n) and polydispersities (M-w/M-n) of poly(1,3,4-oxadiazole)s were in the range 14,660-21,370 and 2.22.5, respectively. Polyhydrazides and poly(1,3,4-oxadiazole)s were soluble in polar aprotic solvents such as N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, and N,N-dimethylformamide. Furthermore, poly(1,3,4-oxadiazole)s were also found to be soluble in solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, and m-cresol. Transparent, flexible, and tough films of polyhydrazides and poly(1,3,4-oxadiazole)s could be cast from N,N-dimethylacetamide and chloroform solutions, respectively. Both polyhydrazides and poly(1,3,4-oxadiazole)s were amorphous in nature and formation of layered structure was observed due to packing of pentadecyl chains. A decrease in glass transition temperature was observed both in polyhydrazides (143-166 degrees C) and poly(1,3,4-oxadiazole)s (90-102 degrees C) which could be ascribed to internal plasticization effect of pentadecyl chains. The T-10 values, obtained from TG curves, for poly(1,3,4-oxadiazole)s were in the range of 433-449 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 124:1281-1289, 2012
Keywords: 3; 4-oxadiazole)s; Cashew nut shell liquid; pentadecyl; poly(1; polyhydrazides; thermal stability

New atom transfer radical polymerization initiator based on phenolphthalein for the synthesis of bis-allyloxy functionalized polystyrene macromonomers - Patil, Sachin S.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Polymer International, 2015)
A new atom transfer radical polymerization (ATRP) initiator, namely 2-(1,1-bis(4-(allyloxy)phenyl)-3-oxoisoindolin-2-yl)ethyl 2-bromo-2-methylpropanoate, was synthesized starting from phenolphthalein, a commercially available and an inexpensive chemical. Well- defined bis-allyloxy functionalized polystyrene macromonomers (M-n,M-GPC 4800-11 700gmol(-1)) with controlled molecular weight and narrow molecular weight distribution (1.05-1.09) were synthesized using ATRP by varying the monomer to initiator feed ratio. The presence of allyloxy functionality on polystyrene was confirmed by Fourier transform infrared and H-1 NMR spectroscopy. A kinetic study of polymerization revealed pseudo-first-order kinetics with respect to monomer consumption. Initiator efficiency was found to be in the range 0.80-0.95. Matrix-assisted laser desorption ionization time of flight spectra showed a narrow molecular weight distribution with control over the molecular weight. The reactivity of the allyloxy groups on polystyrene was successfully demonstrated by quantitative photochemical thiol-ene click reaction with benzyl mercaptan as the model thiol reagent. Furthermore, the thiol-ene click reaction was exploited to introduce other reactive functional groups such as hydroxyl and carboxyl by reaction of ,-bis-allyloxy functionalized polystyrene with 2-mercaptoethanol and 3-mercaptopropionic acid, respectively. (c) 2014 Society of Chemical Industry
Keywords: atom transfer radical polymerization; bis-allyloxy functionalized polystyrene; functional initiator; phenolphthalein; thiol-ene click reaction